Comparative Analysis of Materials in Recreational Boat Design: Fiber Reinforced Plastic Boat in Serial Production - Gölpınar, Serden; Erkarslan, Önder (Izmir Institute of Technology, 2005)
This study aims to reveal the suitable boat construction material for serial production and the innovative design opportunities for the competition in the boat market in which the manufacturers and designers have to differentiate themselves by innovative designs, attractive products and new production techniques.Although the building material, from which the vessel is to be built, has the most important affect on design and production, the material choice and construction methods are first determined in design stage. Thus as the second chapter after introduction, the design stage is presented, which affect product sale more than the others. This chapter is formed by introducing the vessel characteristic, design requirements, design process and design methods, which form the boat. In addition, the computer.s role, which brings a lot of easiness, cost and time advantage to area of boat design, is mentioned.The materials used for boat construction are important for design process. So during the third chapter the materials such as steel, ferrocement, aluminium, wood and composite materials are discussed. By the help of this discussion, a designer can get an idea for the suitable material for his her design and by the help of the comparison graphics of materials he she can get a quick idea about the differences of the materials.Materials used in boat construction have taken up within the framework of a comparison consisting of material.s mechanical characteristics, resistance to different affects, design opportunities and cost. As the result of material comparison, FRP (fiber reinforced plastic) recreational boat construction methods, which are conventional method such as hand lamination and spray lamination and more industrialized techniques such as vacuum bag and SMC etc., are presented in chapter four. In addition, future trends of FRP boat building and computer application (CNC milling), which give the advantages such as time labor and cost save, are presented in chapter four. Finally with this research someone as a designer or manufacturer can create more effective products, which cover the consumer demand, in considering design process, material characteristic and production techniques mentioned in the thesis.
Thesis (Master)--Izmir Institute of Technology, Industrial Design, Izmir, 2005
Includes bibliographical references (leaves: 77)
Text in English; Abstract: Turkish and English
xii, 136 leaves
Keywords: VM321 .G54 2005; Boats and boating--Design and construction; Boats and boating--Materials; Boatbuilding; Fiber reinforced plastics